Measuring Geographic and Wealth Inequalities in Health Distribution as Tools for Identifying Priority Health Inequalities and the Underprivileged Populations - Sherine Shawky DrPH (SAGE Publishing, 2018)
Background Currently, there is no consensus on standard measure that can be routinely part of the health information systems to alert countries to inequalities in health and identify the priority health inequality conditions. Objectives To identify the health inequality measures relevant for assessing geographic and wealth inequalities; use the measures as a demonstration to what can happen in practice to recognize the geographic and wealth-related priority health inequalities within a country; and identify the geographic and wealth underprivileged populations. Method Egypt data were used as demonstration. Pearson coefficient of correlation was calculated to compare the various geographic and wealth health inequality measures. T test was used to identify significant correlations. The relevant inequality measures were used to rank geographic and wealth health inequalities and identify the underprivileged populations. Results The wealth inequalities in health measured by the concentration index provide a familiar and perform adequately in identifying economic inequalities in health. However, the geographic health inequalities identified by the index of dissimilarity appear to provide a more comprehensive profile of health inequalities within a country. Conclusion There is a need for a feasible inequality measure in the health information systems. A country's geographic health distribution measured by the index of dissimilarity appears to provide a feasible first-step alarm to inform and guide the uptake of equity-sensitive policies.